Komercyjne znaczenia leksemu sztuka na przykładzie wybranych tekstów reklam - Łuc, Izabela (Słowo. Studia językoznawcze, 2014)
The aim of the article is to describe the phenomenon, in which the lexeme art acquires a commercial meaning. The gathered body of advertisements broadcast and published in the mass media between 2010 and 2013 shows how the lexeme art corresponds semantically with other language units, thus creating unconventional combinations, and what they, according to the senders, mean (what role was ascribed to them), and also how they influence the consumerist behaviour of the receivers.